HOSPITAL PHYSIOLOGICAL MONITORING SYSTEM - Saleh Hassan, Abbas; Talal Hussein, Raoof (Journal of Engineering and Sustainable Development, 2019)
While a large number of aged people are subject to heart disease, the need to a monitoring system that early detect the disease is increased. In this work physiological parameters, such as pulse rate, Temperature of human are measure through the proposed system. This system designed using Arduino, heart rate sensor, temperature sensor, and LCD.